1987
DOI: 10.1016/0014-5793(87)81253-x
|View full text |Cite
|
Sign up to set email alerts
|

Affinity modification of E1‐form of Na+, K+ ‐ATPase revealed Asp‐710 in the catalytic site

Abstract: An alkylating ATP analogue, y-[4-(N-2-chlorethyl-N-methylamino)]henzylamide ATP (CIRATP), covalently binds to the catalytic a-subunit of Na+,K+-ATPase yielding a product resistant to hydrolysis by the enzyme and inhibiting the ATP-hydrolysing activity. The Naf-form of the membrane-bound Na+,K+-ATPase modified with ClRATP was hydrolysed by pepsin under conditions providing maximum stability of the modification product (4°C pH 1 S). The modified peptide was isolated by HPLC and its amino acid sequence was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 12 publications
1
33
0
Order By: Relevance
“…Previously, this segment was proposed to engage in ATP binding on basis of chemical labeling with FSBA 1 of Lys 719 (7) or with ␥-[4-(N-2-chlorethyl-N-methylamino)]benzylamide ATP at Asp 710 or Asp 714 (8). Lane et al (9) concluded that Asp 712 and Asp 716 of the rat ␣1-subunit are both essential, because HeLa cells expressing substitutions for Asn did not survive in ouabain medium.…”
mentioning
confidence: 99%
“…Previously, this segment was proposed to engage in ATP binding on basis of chemical labeling with FSBA 1 of Lys 719 (7) or with ␥-[4-(N-2-chlorethyl-N-methylamino)]benzylamide ATP at Asp 710 or Asp 714 (8). Lane et al (9) concluded that Asp 712 and Asp 716 of the rat ␣1-subunit are both essential, because HeLa cells expressing substitutions for Asn did not survive in ouabain medium.…”
mentioning
confidence: 99%
“…As mentioned above, in the animal EIE2-ATPases this site is evidently formed by conservative regions of the polypeptide chain of the catalytic subunits in the cytoplasmic portion of the enzyme molecules. Analysis of these regions for the presence of permissive consensus sequences [37] and characteristic elements of the secondary structure [38] may evidence that within the nucleotide-binding site of ion-transporting ATPases the B-a" structure (residues 240-265) encoded by the initial part of exon 8 is present in addition to the structure coded by the initial part of exon 16-a target for affinity modification with the ATP analogue [28,[39][40][41]. The data concerning interrelations of intron positions and structural elements of the proposed nucleotide binding domains require thorough analysis and will be published.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, based on these considerations and the overall sequence identity, we suggest that the nomenclature used for R. sylvatica and R. clamitans Ca 2ϩ -ATPases that are encoded by the cloned cDNAs be SERCA1a as it was proposed earlier for R. esculenta (7). The hydrophobic putative transmembrane domains (M1-M10), the phosphorylation site (residues 349 -355), as well as sites known to bind fluorescein isothiocyanate or the ATP analogues FSBA and CIRATP in SERCA1 (27)(28)(29) are conserved in R. sylvatica SERCA1a. There are five nonconservative amino acid substitutions (Asn, Gln, Ala, Ser, and Leu) characteristic for R. sylvatica (Fig.…”
mentioning
confidence: 86%